Spectral analysis highlight developmental EEG changes in preterm infants without overt brain damage. (10th May 2017) - Suppiej, Agnese; Cainelli, Elisa; Cappellari, Ambra; Trevisanuto, Daniele; Balao, Laura; Di Bono, Maria Grazia; Bisiacchi, Patrizia S.
Highlights: EEG spectral analysis is a useful tool for exploring early brain functioning. EEG spectral analysis highlight different brain maturation in extreme prematurity. Alterations in spectral EEG correlate with outcome at one year of age. Abstract: Early markers of neurological outcome in the absence of overt brain damage are scarce in extreme prematurity. The aim of this study was to compare spectral EEG values of infants born near term with those of infants born at extremely low gestational age (ELGA) but having attained near term age. We aimed also to evaluate whether spectral EEG features were related with neurological outcome. The ELGA group consisted of 12 neonates born between 23 + 2 and 27 + 6 weeks; the control group consisted of nine infants born 34–35 + 2 weeks, tested within the first week of life. All neonates underwent multichannel EEG recordings at 35 weeks post-conception. None of the subjects had apparent neurological abnormalities or risk factors at the time of recording. EEG data were transformed into the frequency domain and divided into delta (0.5–4 Hz), theta (5–7 Hz), alpha (8–13 Hz), beta (14–20 Hz) frequency bands; relative EEG power values were calculated. ELGA group was compared with the control group using a mixed analysis of variance. Outcome was evaluated at one year of age by Griffiths' scales. A principal effect of frequency and an interaction effect of frequency * group was found. The total relative power of the delta band was significantly higher in ELGA than in control group, whereas in the remaining frequency bands total relative power was lower in ELGA than in control group. Higher values of delta and lower values of alpha and beta spectral power correlated with poor outcome. We provide preliminary results suggesting that, as early as 35 weeks post conception, infants born extremely preterm fail to develop the age specific pattern of EEG spectral activity, in the absence of neurological neonatal risk.